Biopsychosocial assessment of dental neglect in a pediatric cancer patient from the perspectives of developmental trauma disorder. Issue 1 (April 2022) - Kobayashi, Kenichiro; Koyama, Noriaki; Nagano, Yugo; Usami, Ikuya; Fujimura, Kazuma; Heike, Toshio
Abstract: A nine-year-old male developed severe opportunistic apical periodontitis in maxillary permanent first molars following myeloablative anticancer therapy for T cell lymphoblastic lymphoma. His developmental trajectory was characterized by limited dental care adherence, maltreatment and developmental trauma disorder, suggesting that a complex interplay between premorbid dental neglect and chemotherapy-related toxicity had exacerbated the progression of the dental infection. We would like to stress the importance of biopsychosocial assessment for severe periodontal infection to provide individualized supportive intervention, thereby improving the quality of life of patients with poor oral health literacy.